Kreativitas dalam Desain Iklan Rokok di Jawa, 1930-1970an - Yuhana Setianingrum (Lembaran Sejarah, 2012)
This paper, entitled ‘The development of cigarette advertising design in Java in 1930 – 1970s’, discusses the transformation of cigarette advertising design. It also discusses the influence of colonial and post-colonial political regimes and the modernization in cigarette advertising visualization between 1930 – 1970s. Research is focused on observation of advertising elements, such as headline, body-copy, illustration, and the art of appearance. These were obtained from the primary sources, such as newspapers, which were published during the period. Secondary sources were also used, for example, relevant books. Based on observation and analysis of cigarette advertisements, it is obvious that the creativity in cigarette advertising design continued to grow, and visual transformation from manual illustration to photo technology occured in the period under study. In addition, there were representations of symbols in cigarette advertising design because of the influence of colonial and post-colonial political regimes and because of the process of modernization.